Identification, Functional Characterization, and Regulon Prediction of the Zinc Uptake Regulator (zur) of Bacillus anthracis – An Insight Into the Zinc Homeostasis of the Pathogen - Kandari, Divya; Gopalani, Monisha; Gupta, Manish; Joshi, Hemant; Bhatnagar, Sonika; Bhatnagar, Rakesh (Frontiers in Microbiology, 2019)
Zinc has an abounding occurrence in the prokaryotes and plays paramount roles including catalytic, structural, and regulatory. Zinc uptake regulator (Zur), a Fur family transcriptional regulator, is connoted in maintaining zinc homeostasis in the pathogenic bacteria by binding to zinc and regulating the genes involved in zinc uptake and mobilization. Zinc homeostasis has been marginally scrutinized in Bacillus anthracis, the top-rated bio-terror agent, with no decipherment of the role of Zur. Of the three Fur family regulators in B. anthracis, BAS4181 is annotated as a zinc-specific transcriptional regulator. This annotation was further substantiated by our stringent computational and experimental analyses. The residues critical for zinc and DNA binding were delineated by homology modeling and sequence/structure analysis. ba zur existed as a part of a three-gene operon. Purified BaZur prodigiously existed in the dimeric form, indicated by size exclusion chromatography and blue native-PAGE. Computational and manual strategies were employed to decipher the putative regulon of ba zur, comprising of 11 genes, controlled by 6 promoters, each harboring at least one Zur box. The DNA binding capability of the purified BaZur to the upstream regions of the ba zur operon, yciC, rpmG, znuA, and genes encoding a GTPase cobalamine synthesis protein and a permease was ascertained by electrophoretic mobility shift assays. The regulon genes, implicated in zinc uptake and mobilization, were mostly negatively regulated by BaZur. The ba zur expression was downregulated upon exposure of cells to an excess of zinc. Conversely, it exhibited a marked upregulation under N, N, N′, N′-Tetrakis (2-pyridylmethyl) ethylenediamine (TPEN) mediated zinc-depleted environment, adding credence to its negative autoregulation. Moreover, an increase in the transcript levels of the regulon genes znuA, rpmG, and yciC upon exposure of cells to TPEN connoted their role in combating hypo-zincemic conditions by bringing about zinc uptake and mobilization. Thus, this study functionally characterizes Zur of B. anthracis and elucidates its role in maintaining zinc homeostasis.